Effects of a 30-min rest with a nap chair on task performance, sleepiness, and neurophysiological measures in men with suspected brain fatigue: a randomized controlled crossover trial - Fujino, Minoru; Inoue, Mikio; Sonoda, Yoshiharu; Kono, Suminori; Wakana, Chikako; Mawatari, Shiro; Fujino, Takehiko (Frontiers in Sleep, 2024)
Background: It has been suggested that a short nap in the afternoon may improve sleepiness, alertness, and task performance. The present study evaluated the effects of a 30-minute rest with a new nap chair on task performance, sleepiness, and neurophysiological measures. Methods: A randomized controlled crossover trial with a 1-week interval was carried out at the BOOCS Clinic Fukuoka in Japan. The subjects were male workers aged 20 to 64 years with suspected brain fatigue, which was defined by the Profile of Mood Status 2. The intervention was a 30-minute rest with an office-chair or a nap chair. The primary outcome was the performance in the Uchida-Kraepelin test. The secondary outcomes included the Karolinska Sleepiness Scale and 15-minute heart rate variability (HRV). The changes after the nap-chair rest and office-chair rest were compared. Repeated measures analysis of variance with nesting was used in the statistical analysis. Results: Twenty participants were eligible and entered the cross over trial. The overall 15-minute score in the Uchida-Kraepelin test improved after the nap-chair rest and after the office-chair rest to almost the same extent (5.9 versus 5.5 points, P = 0.68). The Karolinska Sleepiness score significantly decreased after the nap-chair rest, and the between-treatment difference in the decrease was highly significant (P = 0.0004). The average duration of sleep during rest was prominently longer in the nap-chair rest than in the office-chair rest (19.0 versus 7.6 minutes, P = 0.002). No participants experienced REM sleep during the rest. LF and HF powers of the HRV were greater during the nap-chair rest than during the office-chair rest, the difference in the HF power being substantial. Conclusion: A 30-minute rest with the nap chair did not appreciably improve the performance in the Uchida-Kraepelin test as compared with the office-chair rest. The nap-chair rest induced a substantially longer sleep accompanied with a parasympathetic activation, thereby resulting in a material improvement in sleepiness after the rest.